The Complex World of Ants - Shields, Vonnie (IntechOpen, 2018)
Ants play important roles in natural ecosystems. These eusocial insects are omnivorous feeders and live in a wide variety of habitats. They belong to the order Hymenoptera, and family Formicidae. There are more than 8800 described species that occur throughout the world. They have large heads, segmented antennae, and powerful jaws and undergo complete metamorphosis. In general, ants live typically in structured nest communities, forming nest sites in close proximity to moisture and food, underground, in ground-level mounds, or in trees. Among ant species, there is a wide range of interesting behaviors displayed. Many species are mutualistic, where they develop interactions with other insects and/or plants. Other species display parasitic relationships among each other. Still other species exhibit predatory behaviors. This book contains contributions written by experts in their respective fields and targets a wide audience. It is highly recommended as a valuable resource for general biologists, entomologists, ecologists, zoologists, and students and teachers in training in this subject matter.